Raman scattering quantitative assessment of the anion composition ratio in Zn(O, S) layers for Cd-free chalcogenide-based solar cells. Issue 29 (3rd March 2016) - Guc, M.; Neuschitzer, M.; Hariskos, D.; Bauer, A.; Witte, W.; Hempel, W.; Calvo-Barrio, L.; Pistor, P.; Perez-Rodriguez, A.; Izquierdo-Roca, V.
Abstract : This work reports the use of Raman scattering for the chemical characterization of Zn(O, S) layers that are being developed as a Cd-free alternative for the buffer layer in advanced chalcogenide solar cells. Abstract : This work reports the use of Raman scattering for the chemical characterization of Zn(O, S) layers that are being developed as a Cd-free alternative for the buffer layer in advanced chalcogenide solar cells. The nanometric thickness of these layers requests the use of resonant excitation conditions, which are strongly sensitive to the alloy composition. In this study Raman spectra were measured with different excitation wavelengths (325 nm, 532 nm) on a set of reference samples with chemical compositions covering the whole range from stoichiometric ZnS to stoichiometric ZnO. The results show the existence of a strong linear dependence of the frequency of the ZnO-like peak on the alloy composition, which provides a simple methodology for the quantitative assessment of the chemical composition in almost all the composition region. In the case of samples with a S-rich composition (0.5 ≤ S/(S + O) ≤ 1), the analysis of the relative intensity of the ZnS like peak allows for a complementary assessment of the S/(S + O) content ratio. The characterization of layers grown under conditions similar to those used for the fabrication of chalcogenide solar cells has allowed the demonstration of the viability of the proposed methodology for the non-destructive chemical assessment of these advanced buffer layers.